2015
DOI: 10.1021/acs.joc.5b01418
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent Synthesis of Bis-Spiropyrrolidines via Sequential Interrupted and Completed (3 + 2) Cycloadditions

Abstract: Both (5R)- and (5S)-1,7-diazaspiro[4.4]nonan-6-ones are obtained via a sequence of interrupted and completed stepwise (3 + 2) cycloadditions between azomethine ylides and π-deficient alkenes. The only source of chirality along the whole process is an enantiopure ferrocenyl pyrrolidine catalytic ligand. When the starting imine incorporates two aryl groups or one aryl group with one electron-releasing substituent, the reaction between the azomethine ylide and the alkene stops at the first step, leading to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Alternatively, an additional phenyl group present in imines 31 derived from acetophenone is able to frustrate the cycloaddition but, in this case, only anti ‐γ‐nitro‐α‐amino esters 32 were obtained in the presence of the same chiral ligand NH‐ d ‐EhuPhos 25 (Scheme ). Also in this case, DFT calculations permitted to rationalize these different stereochemical outcomes . It is also noteworthy that, once again, NH‐ d ‐EhuPhos , an unnatural d ‐Proline ester, promoted the formation of l ‐amino esters via these frustrated (3+2) cycloadditions.…”
Section: Synthesis Of Catalysts By Means Of 13‐dipolar Reactionsmentioning
confidence: 77%
See 3 more Smart Citations
“…Alternatively, an additional phenyl group present in imines 31 derived from acetophenone is able to frustrate the cycloaddition but, in this case, only anti ‐γ‐nitro‐α‐amino esters 32 were obtained in the presence of the same chiral ligand NH‐ d ‐EhuPhos 25 (Scheme ). Also in this case, DFT calculations permitted to rationalize these different stereochemical outcomes . It is also noteworthy that, once again, NH‐ d ‐EhuPhos , an unnatural d ‐Proline ester, promoted the formation of l ‐amino esters via these frustrated (3+2) cycloadditions.…”
Section: Synthesis Of Catalysts By Means Of 13‐dipolar Reactionsmentioning
confidence: 77%
“…We reasoned that substituents that stabilize positive charges on the iminium moieties of these intermediates could frustrate the completion of the second step of the (3+2) cycloaddition, thus permitting the chemical synthesis of γ‐nitro‐α‐amino esters and their derivatives. In effect, we found that in the presence of 1 equiv. of NH‐ d ‐EhuPhos 25 and at –60 °C, reaction of nitroalkenes with imines 27 derived from 4‐methoxybenzaldehyde permitted to isolate syn ‐γ‐nitro‐α‐amino esters 31 with excellent enantiocontrol (Scheme ).…”
Section: Synthesis Of Catalysts By Means Of 13‐dipolar Reactionsmentioning
confidence: 85%
See 2 more Smart Citations
“…A series of enantiopure tetrasubstituted nitroprolinate surrogates has been designed as scaffolds for proteasome inhibitors with high medicinal prospects . In addition, the NH−D−EhuPhos ligand 7 has been efficiently employed in the 1,3‐dipolar cycloadditions (1,3‐DC) to yield nitroprolinates and structurally rigid spirocompounds from chiral γ‐lactams . exo ‐ 6 a Series were employed as amino component in the multicomponent amino−aldehyde−dienophile (AAD) reaction affording chiral cyclohex‐2‐enyl amines and in two different multicomponent 1,3‐cycloadditions furnishing pyrrolizidines …”
Section: Introductionmentioning
confidence: 99%